Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1017/sjp.2018.68
|View full text |Cite
|
Sign up to set email alerts
|

Unemployment, Self-esteem, and Depression: Differences between Men and Women

Abstract: Although there is a vast bibliography on the negative consequences of unemployment for mental health, there are no studies that analyze the differences between men and women in relation to the consequences that unemployment could have simultaneously on self-esteem and depression. The main objective of this study was to analyze whether, unemployment is differentially associated with the self-esteem of men and women, and to test whether this circumstance can be considered a psychological mechanism by which we co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 31 publications
4
31
1
2
Order By: Relevance
“…Our results also extend the understanding of these relationships by suggesting that financial hardship may tend to affect women's mental health, while job loss may impact men's mental health, aligning with findings from a systematic review that found that men were more likely to experience poor mental health as a result of unemployment as compared to women [31]. Research suggests that men are more likely to feel isolated [32] and experience a higher loss of self-esteem [33] due to job loss as compared to women. Loss of employment can be stigmatizing for men in patriarchal societies, such as India, where norms of masculinity are intricately linked to employment status [34].…”
Section: Discussionsupporting
confidence: 85%
“…Our results also extend the understanding of these relationships by suggesting that financial hardship may tend to affect women's mental health, while job loss may impact men's mental health, aligning with findings from a systematic review that found that men were more likely to experience poor mental health as a result of unemployment as compared to women [31]. Research suggests that men are more likely to feel isolated [32] and experience a higher loss of self-esteem [33] due to job loss as compared to women. Loss of employment can be stigmatizing for men in patriarchal societies, such as India, where norms of masculinity are intricately linked to employment status [34].…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, the same scenario is present on a relational level, with subjects who continued to have sexual intercourses during lockdown showing better scores on dyadic cohesion and satisfaction subscales of DAS-32, confirming the evidence that a regular sexual activity leads to a better relational health. 36 Not differently from other clinical sets, female gender is more likely to develop anxiety and mood disorders. 37,38 Our data agree with evidence regarding both the worsening of the psychological well-being during COVID-19erelated social isolation 39,40 and the historical knowledge about the major female susceptibility to the development of emotional diseases 39 and sexual dysfunctions.…”
Section: Discussionmentioning
confidence: 99%
“…Males, in particular, may experience lower self‐worth when unemployed, whereas unemployed female residents may be more likely to engage in unpaid activities that contribute to self‐worth, such as caregiving. Relatedly, previous research has shown that among male but not female residents, unemployment was associated with lower self‐esteem, which in turn was related to greater depression symptoms, though such work has not previously focused on Hispanics/Latinos residing in the US (Álvaro et al, 2019). Another possible explanation is that female residents are often more likely to engage in community activities that support social capital and self‐worth (Ahern & Hendryx, 2008; Bassett & Moore, 2013).…”
Section: Discussionmentioning
confidence: 99%